Apakah Ukuran Perusahaan, Kompleksitas Perusahaan, Leverage, Profabilitas dan Komite Audit Mempengaruhi Biaya Audit? - Rifaldi, Muhamad Rifay (Politeknik Ganesha Medan, 2024)
Audit Fee is the amount of imbalance that will be accepted by public accountants by adjusting the assignment, complexity of services and level of expertise related to providing financial report audit services. Rules regarding Audit Fees were made by the Indonesian Institute of Public Accountants (IAPI) in Management Regulation Number 2 of 2016 concerning